2003
DOI: 10.4319/lo.2003.48.1_part_2.0412
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the fluorescence of the Caribbean coral Montastraea faveolata during heat‐induced bleaching

Abstract: In order to evaluate the response of commonly occurring green and orange fluorescent host-based pigments, a thermal stress experiment was performed on specimens of the Caribbean coral Montastraea faveolata. Seven paired samples were collected from a small oceanic reef near Lee Stocking Island in the Bahamas. Seven of the fourteen corals were subjected to elevated temperatures for 28 d, followed by a recovery period lasting 53 d. Throughout the experiment, high-resolution (ϳ400 m pixel Ϫ1 ) multispectral images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
(53 reference statements)
0
23
2
Order By: Relevance
“…First, we used fluorescence information to improve the classification accuracy of the dominant benthic classes by 2.7%, which is equivalent to a 22% relative reduction of error-rate. In contrast to previous work that investigated the use of fluorescence spectra to classify groups defined by their level of bleaching [93], fluorescence signatures [148,88], or other physiological states [118,149,36], our work provides evidence that the fluorescence signatures can be directly related to benthic taxonomy. Second, most work on coral fluorescence has relied on relatively expensive spectrometers or custom multi-spectral cameras which have high spectral but limited spatial resolution [148,88].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…First, we used fluorescence information to improve the classification accuracy of the dominant benthic classes by 2.7%, which is equivalent to a 22% relative reduction of error-rate. In contrast to previous work that investigated the use of fluorescence spectra to classify groups defined by their level of bleaching [93], fluorescence signatures [148,88], or other physiological states [118,149,36], our work provides evidence that the fluorescence signatures can be directly related to benthic taxonomy. Second, most work on coral fluorescence has relied on relatively expensive spectrometers or custom multi-spectral cameras which have high spectral but limited spatial resolution [148,88].…”
Section: Discussioncontrasting
confidence: 49%
“…Multispectral cameras, underwater spectrometers, underwater radiometers and underwater fluorometers (diving PAMs) have been previously used to quantify physiological parameters of coral reef organisms [133]. Another option is to measure fluorescence signatures which have been shown to contain ecologically relevant information such as level of bleaching [93], recruitment levels [133], and physiological state [149]. However, until recently, fluorescence imaging systems were limited either by resolution [149], spatial coverage of the measurements [87,147] and/or ease of operation [87,149,88].…”
Section: Introductionmentioning
confidence: 99%
“…In a heat stress experiment of Montastrea faveolata, the ratio of green to orange fluorescence switched when corals bleached and eventually died, then being mainly orange52. However, it was not determined if the source of the orange fluorescence was from coral FPs or phycoerythrin from endosymbiotic cyanobacteria53.…”
Section: Discussionmentioning
confidence: 99%
“…Emission in red, at wavelengths longer than 630 nm, is not generated by the coral host (Mazel 1995, Salih et al 2000., Neori et al 1988), but from photosynthetic pigments found in their algal symbionts (Jeffrey and Haxo 1968), which show a distinct chlorophyll peak at 680 nm (red light) when excited with blue light (480 nm) (Gurskaya et al 2001). The detected rise in red fluorescence for corals in low oxygen treatments may therefore either be attributed to increases in zooxanthellae (yet unlikely since the corals were bleached and dying), or to the growth of endolithic algae (already present in the coral skeleton), cyanobacteria and/or filamentous algae starting to colonize the bare coral skeleton (Shashar et al 1997;Zawada and Jaffe 2003).…”
Section: Red Fluorescencementioning
confidence: 99%